FRI0054 A long-term, open-label trial of the safety and efficacy of etanercept (25 mg twice weekly) in patients with rheumatoid arthritis (interim analysis). (1st June 2001) - Willis, RF; Pedersen, R
Abstract : Background: Several double-blind, placebo-controlled studies previously demonstrated that etanercept was safe and efficacious in treating rheumatoid arthritis (RA) patients who had an inadequate response to disease-modifying antirheumatic drugs (DMARDs). Objectives: To evaluate the long-term safety and efficacy of etanercept in patients who completed prior double-blind clinical studies comparing etanercept to placebo. Methods: As reported in previous updates, 549 patients entered this 4-year, open-label study and began treatment with etanercept 25 mg twice weekly at 58 centres in Europe following completion of double-blind clinical studies. All patients previously had inadequate responses to DMARDs. Safety assessments were performed at regular intervals to determine the incidence of treatment emergent adverse events including malignancies and serious infections (those associated with hospitalisation and/or the administration of intravenous antibiotics). The numbers of painful and swollen joints were predefined as primary efficacy endpoints; other efficacy measures included ACR response rates and acute phase reactants. Efficacy was analysed with the last observation carried forward (LOCF). Results: Of the 549 patients initially enrolled, 437 (80%) are currently active, 479 (87%) completed 1 year, and 94 (17%) completed 2 years. A total exposure of 927 patient-years has been accrued. The rate of withdrawal from the study was similar for efficacy- and tolerance-related reasons (7% and 8%, respectively). Adjusted for patient exposure, the most frequent adverse events were injection site reactions and upper respiratory infections. Rates of serious infections and malignancies have remained unchanged over the course of the study. Maintained efficacy was observed as demonstrated by a mean 71% and 72% reduction in painful and swollen joint counts, respectively. Similar to results measured at the early time points of this open-label trial, ACR 20, 50, and 70 response rates were determined to be 79%, 47%, and 25%, respectively, as patients approached two years of treatment. Conclusion: Following the accumulation of substantial exposure in patients with RA, etanercept demonstrates an acceptable safety profile and continues to provide significant and maintained clinical benefit.